Perilaku Konsumen Dan Upayanya Dalam Pelayanan Prima Bagi Pelanggan - Djaka Suryadi (Jurnal Asy-Syukriyyah, 2019)
Service Excellent, now has become a necessity for all lines of business, micro, retail, commercial and corporate, and now the success of a business occurs because entrepreneurs have to pick up their customers, so customers will always feel pampered in fulfilling everything their needs. A business failure occurs because customers are disappointed so they look for alternatives to other similar products. Consumers increasingly dare to protest and complain when the service they get is bad. Consumers have higher standards of service and satisfaction which means it is increasingly difficult for consumers to feel satisfied. The consumer approach to being loyal (customer loyalty) should be based on customer needs carried out carefully, focused, systematically and effectively. quality service and always done re-engineering services in a manner that is expected to be able to satisfy customers and always try to make customers who are always defending their company (advocate).